Analisa Polemik Dan Apologi Pemekaran Provinsi Baru Dalam Penyelenggaraan Dan Penerapan Otonomi Daerah - Dwi Putra Nugraha; Daafa’a Alhaqqy Muhammad (Law, Development and Justice Review, 2022)
Otonomi Daerah, as stated in UU No. 32/2004, is the right, authority, and obligation of autonomous regions to regulate and manage their own government affairs and the interests of local communities in accordance with statutory regulations. With regional autonomy, it is hoped that decentralisation that supports equity in terms of development and welfare can be realized. The ideal conditions that are expected with the implementation of regional autonomy are very far from the current reality One in particular is Banten Province, which departed from West Java Province since 2000 and whose poverty level has actually increased. This research was done to show that the ideal conditions that are expected with the implementation of regional autonomy are very far from the current reality. Report cards for new autonomous regions, including Banten Province, are still dominated by red numbers. Keyword: Regional autonomy, decentralization, participation and local elit Abstrak  Otonomi daerah sebagaimana tertuang dalam UU No. 32/2004 adalah hak, wewenang, dan kewajiban daerah otonom untuk mengatur dan mengurus sendiri urusan pemerintahan dan kepentingan masyarakat setempat sesuai dengan peraturan perundang-undangan. Dengan otonomi daerah, diharapkan desentralisasi yang mendukung pemerataan pembangunan dan kesejahteraan dapat terwujud. Kondisi ideal yang diharapkan dengan pelaksanaan otonomi daerah sangat jauh dari kenyataan saat ini Salah satunya adalah Provinsi Banten yang berangkat dari Provinsi Jawa Barat sejak tahun 2000 yang tingkat kemiskinannya justru meningkat. Studi ini dilakukan untuk menunjukkan kondisi ideal yang diharapkan dengan dilaksanakannya otonomi daerah nyatanya sangat jauh dari kenyataan saat ini. Raport untuk daerah otonom baru, khususnya Provinsi Banten, masih didominasi angka merah.